CqZF-HD14 enhances drought tolerance in quinoa seedlings through interaction with CqHIPP34 and CqNAC79 - Sun, Wenjun (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2022 Elsevier B.V. All rights reserved.